Patient-centered recruitment and retention for a randomized controlled study - Chhatre, Sumedha; Jefferson, Ashlie; Cook, Ratna; Meeker, Caitlin R.; Kim, Ji Hyun; Hartz, Kayla Marie; Wong, Yu-Ning; Caruso, Adele; Newman, Diane K.; Morales, Knashawn H.; Jayadevappa, Ravishankar (Current controlled trials in cardiovascular medicine, 2018)
Recruitment and retention strategies for patient-centered outcomes research are evolving and research on the subject is limited. In this work, we present a conceptual model of patient-centered recruitment and retention, and describe the recruitment and retention activities and related challenges in a patient-centered comparative effectiveness trial. This is a multicenter, longitudinal randomized controlled trial in localized prostate cancer patients. We recruited 743 participants from three sites over 15 months period (January 2014 to March 2015), and followed them for 24 months. At site 1, of the 773 eligible participants, 551 (72%) were enrolled. At site 2, 34 participants were eligible and 23 (68%) enrolled. Of the 434 eligible participants at site 3, 169 (39%) enrolled. We observed that strategies related to the concepts of trust (e.g., physician involvement, ensuring protection of information), communication (e.g., brochures and pamphlets in physicians' offices, continued contact during regular clinic visits and calling/emailing assessment), attitude (e.g., emphasizing the altruistic value of research, positive attitude of providers and research staff), and expectations (e.g., full disclosure of study requirements and time commitment, update letters) facilitated successful patient recruitment and retention. A stakeholders' advisory board provided important input for the recruitment and retention activities. Active engagement, reminders at the offices, and personalized update letters helped retention during follow-up. Usefulness of telephone recruitment was site specific and, at one site, the time requirement for telephone recruitment was a challenge. We have presented multilevel strategies for successful recruitment and retention in a clinical trial using a patient-centered approach. Our strategies were flexible to accommodate site-level requirements. These strategies as well as the challenges can aid recruitment and retention efforts of future large-scale, patient-centered research studies. Clinicaltrials.gov , ID: NCT02032550 . Registered on 22 November 2013.